Innovation And Branding Strategy Of Local Food MSMES To Increase Competitiveness In Kupang City - Enike Tje Yustin Dima; Agnes Susanti Indrawati; Maximilianus Paulus Jati Gamatara (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Objective: This study examines how product innovation and branding strategy influence the competitiveness of local food MSMEs in Kupang City, with e-commerce adoption positioned as a mediating variable. Design/Methods/Approach: A quantitative approach was employed using SEM-PLS based on survey data from 258 local food MSMEs in Kupang City collected through purposive sampling. Findings: Product innovation and branding strategy have positive and significant direct effects on MSME competitiveness. Branding strategy has a strong and significant effect on e-commerce adoption, while product innovation does not. E-commerce adoption does not significantly affect competitiveness and does not mediate the relationships between innovation/branding and competitiveness. Originality/Value: This study integrates product innovation, branding strategy, and e-commerce adoption in a single empirical model for local food MSMEs, providing evidence from an underexplored regional context (Kupang City, East Nusa Tenggara). Practical/Policy implication: MSME development programs should prioritize innovation and branding assistance, while digital interventions should focus on improving digital readiness (skills, logistics, and infrastructure) so e-commerce can contribute effectively.